Effects of exercise‐induced apelin levels on skeletal muscle and their capillarization in type 2 diabetic rats. Issue 6 (21st March 2017) - Son, Jun Seok; Kim, Hee‐Jae; Son, Yeri; Lee, Hojun; Chae, Song Ah; Seong, Je Kyung; Song, Wook
ABSTRACT: Introduction: Exercise‐induced apelin as a myokine is believed to play a role in the improvement of type 2 diabetes mellitus (T2DM) and capillarization. In this study, we evaluated the association between exercise‐induced apelin and muscle capillarization. Methods: Zucker rats underwent a treadmill exercise program. Body composition, muscle strength, muscle size, muscle capillarization, and insulin resistance (homeostatic model assessment [HOMA‐IR]) were measured. Apelin levels of skeletal muscle and plasma were then analyzed. Results: Exercise improved body composition ( P  < 0.05), HOMA‐IR ( P  < 0.05), and grip strength ( P  < 0.001). In the soleus, the fiber size of T2DM was decreased ( P  < 0.001), but it increased in fiber size and capillarization after exercise ( P  < 0.001) occurred. We identified an increase in plasma apelin ( P  < 0.05) and a decrease in soleus apelin ( P  < 0.01), as well as an association between soleus apelin and angiogenesis ( P  < 0.01). Discussion: A role for exercise‐induced apelin in improving metabolism indicates the possibility of a new drug target for the treatment of metabolic diseases and repairing skeletal muscle damage. Muscle Nerve 56 : 1155–1163, 2017